IMPLEMENTING A QUALITY MANAGEMENT SYSTEM AT THE NORTH!WESTERN REGIONAL CENTER OF FORENSIC SCIENCE OF THE RUSSIAN MINISTRY OF JUSTICE - N. Zamaraeva (Теория и практика судебной экспертизы, 2014)
The paper presents a summary of e!orts to implement a system of quality managementin one of Russia's forensic science organizations, in compliance with the framework forcontinuous improvement of forensic science laboratories across Europe, and for thepurposes of ISO accreditation.